INSTITUTE OF REFUGEES IN KAZAKHSTAN LAW: COMPARATIVE LEGAL ANALYSIS (Journal of actual problems of jurisprudence, 2026)
The article is devoted to the study of the institution of refugees within the legal system of the Republic of Kazakhstan in the context of international legal standards. Based on a comparative legal analysis, it examines regulatory legal acts governing the status of refugees, identifies gaps in national legislation, and proposes ways to harmonize it with universal international obligations. Particular attention is paid to the legal mechanisms for recognizing refugee status, guarantees of rights, and access to social protection. The influence of the 1951 United Nations Convention, the legislation of the European Union, and the practice of the UN Human Rights Committee is analyzed. Conclusions are drawn regarding the need to strengthen institutional mechanisms of law enforcement and ensure the systematic implementation of international standards into the national jurisdiction. The importance of improving procedures for considering asylum applications is emphasized, including ensuring transparency, procedural fairness, and compliance with the principle of non-refoulement as one of the fundamental principles of international law. Special attention is also given to the legal status of asylum seekers at the stage of reviewing their applications, as well as to the necessity of providing them with minimum social guarantees. In addition, the article concludes that it is advisable to expand the international cooperation of the Republic of Kazakhstan in the field of refugee protection, including the exchange of experience with foreign states, participation in international programs, and the adaptation of best practices.       Keywords: refugee, asylum, legal status, international law, Kazakhstan, human rights, protection, implementation.